(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The majority of the constitutions of the European socialist states comprise only brief regulations as to the structure and principles behind the functioning of the government. They provide for appropriate formation of a government and vest adequate powers in this respect both with the parliament and the top presiding organ — though with regard to a limited range of problems and temporarily — between the sessions or subsequent terms of the parliament. Both the execution of the powers pertaining to the formation of the government and the ratification of the resolutions passed by the top presiding organ, which concern the membership of the government, furnish the parliament with an opportunity to participate in the formation of the top executive-managing organ. The exceptions to the rule embrace the constitutional provisions of Czechoslovakia (of 1960 and 1968). Jugoslavia (of 1953, 1963 and 1974 — which are in force at present) and Rumania (after the amendments of 1974) where the power to decide about the composition of the government (in Jugoslavia — The Federal Executive Council) has been vested with the president. In Rumania the situation is most complex — the decisions on the formation of the government “in concreto” have been devided among the Grand National Assembly, the Council of State and its president. Under the circumstances when the actual composition of the government is determined by other state organ than the parliament, in terms of the powers vested with the socialist parliament, the latter’s directions which regulate the structure and operation of the top executive-managing organ, are of outstanding significance. However as soon as the regulations are ranked as an act, the structure of the government becomes more stable in legal terms, and the resolutions passed by the parliament, president or the top presiding organ, pertaining to the composition of the government “in concreto”, gain in firm foundations. In this connection a comprehensive statute (in a form of a special “act on government”) seems to be an optimal solution. In several socialist countries the tradition of such a statute has been of a long standing (in the German Democratic Republic).